Perbedaan pH, Viskositas dan Volume Saliva setelah Berkumur dengan Obat Kumur Sintetik yang Mengandung Chlorhexidine dan Larutan Propolis pada Anak Usia 11-12 Tahun - Shinta dinyanti; Roedy Budirahardjo; Raditya Nugroho (Pustaka Kesehatan, 2019)
Dental caries is a process that begins with dissolution of enamel causing damage to the dental component by several factors, such as saliva. The occurrence of diseases in the oral cavity is prevented by the use of synthetic mouthwash containing chlorhexidie, but the using of synthetic compounds causes mutagenic effects on the oral cavity, so it needs alternative by using natural ingredients that have antibacterial power and smaller side effects. The purpose of the study was to investigate the difference of pH, viscosity and volume saliva after gargling with synthetic mouthwash containing of chlorhexidine and propolis solution for children age 11-12 years in Pondok Pesantren Nurul Islam Antirogo Jember. This study used pra-experimental One Shoot Case Study with total sampling in Pondok pesantren Nurul Islam Antirogo Jember. As many 25 students were recruited for the study. The result showed that after gargling with propolis solution can be increase of pH saliva, decrease of viscosity saliva and increase of volume saliva for children age 11-12 years in Pondok Pesantren Nurul Islam Antirogo Jember.